Effect of Cryoprotectants on Long-Term Storage of Oral Mucosal Epithelial Cells: Implications for Stem Cell Preservation and Proliferation Status - Cabral, Joao Victor; Smorodinová, Natálie; Voukali, Eleni; Balogh, Lukáš; Kučera, Tomáš; Kolín, Vojtěch; Studený, Pavel; Vacík, Tomáš; Jirsová, Kateřina (Folia biologica, 2024)
In this study, we tested a method for long-term storage of oral mucosal epithelial cells (OMECs) so that the cells could be expanded in vitro after cryopreservation and used for the treatment of bilateral limbal stem cell deficiency. The ability of suspended primary OMECs to proliferate in vitro after cryopreservation was compared to that of OMEC cultures that had undergone the same process. Both were preserved in standard complex medium (COM) with or without cryoprotective agents (CPAs) (gly-cerol at 5 % or 10 % or dimethyl sulphoxide at 10 %). We found that after cryopreservation, primary OMECs could form a confluent cell sheet only in a few samples after 22 ± 2.9 (mean ± SD) days of cultivation with 72.4 % ± 12.9 % overall viability. Instead, all ex vivo OMEC cultures could re-expand after cryopreservation with a comparable viability of 78.6 ± 13.8 %, like primary OMECs, but with significantly faster growth rate (adj. P < 001), forming a confluent cell sheet at 13.7 ± 3.9 days. Gene expression analyses of the ex vivo expansion of OMEC cultures showed that the stemness, proliferation and differentiation-related gene expression was similar before and after cryopreservation, except for KRT13 expres-sion, which significantly decreased after the second passage (adj. P < 0.05). The addition of CPAs had no effect on these outcomes. In conclusion, the optimal strategy for OMEC preservation is to freeze the cells that have been previously cultured, in order to maintain cell viability and the capacity to create a sizable graft even without CPAs.
Keywords: Gene Expression Regulation; kryoprotektivní látky; viabilita buněk; Male; oral mucosal epithelial cells; epitelové buňky; Cell Proliferation; Cryopreservation; Epithelial Cells; buněčná diferenciace; Cell Survival; mužské pohlaví; Time Factors; limbal stem cell deficiency; Stem Cells; kultivované buňky; cryopreservation; cell culture; Cryoprotective Agents; lidé; Humans; regulace genové exprese; časové faktory; proliferace buněk; cryoprotectives; Cells, Cultured; kryoprezervace; ústní sliznice; kmenové buňky; stemness; Mouth Mucosa; Cell Differentiation